Production of the X(3872) in Pb-Pb collisions at sNN=5.02 TeV from PACIAE model - Xu, Hongge; She, Zhilei; Yu, Ning; Zhang, Zuman (Frontiers in Physics, 2025)
We employed the dynamically constrained phase space coalescence model to study the X(3872), where the parton and hadron cascade model (PACIAE) was used to simulate Pb-Pb collisions at sNN=5.02 TeV in centralities of 0−10% and 30−50%. In this work, we examined the correlation between the yield of the X(3872) and the parameters Δm and R. Additionally, We predicted the yields of the X(3872) for its three plausible configurations, namely, the hadronic molecular state, tetraquark state and nuclear-like state, in Pb-Pb collisions at sNN=5.02 TeV. We also analyzed the transverse momenta for three different structures of the X(3872). Sizable differences were observed in the transverse momentum distributions among the three different X(3872) structures.